2020
DOI: 10.3390/nu12051234
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B Supplementation and Nutritional Intake of Methyl Donors in Patients with Chronic Kidney Disease: A Critical Review of the Impact on Epigenetic Machinery

Abstract: Cardiovascular morbidity and mortality are several-fold higher in patients with advanced chronic kidney disease (CKD) and end-stage renal disease (ESRD) than in the general population. Hyperhomocysteinemia has undoubtedly a central role in such a prominent cardiovascular burden. The levels of homocysteine are regulated by methyl donors (folate, methionine, choline, betaine), and cofactors (vitamin B6, vitamin B12,). Uremia-induced hyperhomocysteinemia has as its main targets DNA methyltransferases, and this le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…A dietary intake of key essential nutrients is important to promote and maintain human health and to reduce health risks across the life span, which can be achieved with a personalized diet [1-6]; however, significant proportions of the population do not consume the recommended daily intake of essential nutrients [7,8]. Inadequate intake of essential macro-and micro-nutrients can lead to mortality, morbidity, and create a burden on healthcare systems [1][2][3][4][5][6]. With the accessibility of modern smartphones, the essential micro-nutrients can be assessed conveniently through internet-based health applications (apps) to enhance healthy nutrigenomics and epigenetics [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A dietary intake of key essential nutrients is important to promote and maintain human health and to reduce health risks across the life span, which can be achieved with a personalized diet [1-6]; however, significant proportions of the population do not consume the recommended daily intake of essential nutrients [7,8]. Inadequate intake of essential macro-and micro-nutrients can lead to mortality, morbidity, and create a burden on healthcare systems [1][2][3][4][5][6]. With the accessibility of modern smartphones, the essential micro-nutrients can be assessed conveniently through internet-based health applications (apps) to enhance healthy nutrigenomics and epigenetics [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Greater vegetable protein intake has been associated with reduced proteinuria and urinary creatinine (62) and reduced mortality among those experiencing CKD (63) . Vitamin B 6 has been shown to inhibit formation of advanced glycation end products (64) , and inadequate folate intake has been associated with hyperhomocysteinemia, which is common in CKD patients (65) . That Hispanic/Latino older adults were consuming some nephroprotective foods and nutrients in greater quantities than older White adults may underly racial/ethnic differences in the observed association between dietary quality and cystatin C change.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in human cohorts found an association between folic acid supplementation during the periconception period and increased methylation in IGF2 in the offspring [ 124 ]. DNA methylation during development is related to methyl donor groups obtained from one-carbon metabolism, so there are several associated studies [ 115 , 119 , 125 , 126 , 127 , 128 , 129 , 130 ].…”
Section: Diet Models and Epigenetic Modifications: Examples And Biological Meaningmentioning
confidence: 99%